2018
DOI: 10.2341/17-130-l
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different CAM Strategies on the Fit of Partial Crown Restorations: A Digital Three-dimensional Evaluation

Abstract: CAM strategy influenced the internal adaptation of zirconia-reinforced lithium silicate partial crowns fabricated with a chairside CAD/CAM system. Sensible selection of specific areas of internal adaptation and fit is an important factor for evaluating the CAM accuracy of CAD/CAM systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 6 publications
3
20
0
Order By: Relevance
“…Literature regarding marginal fit with chairside systems is available for CEREC, but most of them scanned typodont specimens. The mean marginal gap ranged from 94 to 145 μm [16,17]. These results are comparable to this study's CEREC data, considering the difference between the marginal gap and AMD.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Literature regarding marginal fit with chairside systems is available for CEREC, but most of them scanned typodont specimens. The mean marginal gap ranged from 94 to 145 μm [16,17]. These results are comparable to this study's CEREC data, considering the difference between the marginal gap and AMD.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, the AMD measured 71-78 μm for Planmeca models and 132 μm for CEREC, which appears higher than the range of studies included in the meta-analysis. However, in most studies [5,16,17,50], the marginal gap was measured, defined by Holmes to be the closest measurement from the internal surface of the restoration Fig. 5 The gap between crowns and tooth abutment by site and mill system in microns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This might be explained by the milling radius correction of the CAM strategy. Zimmermann et al showed a significant difference in the accuracy of fit for ceramic crowns milled by different CAM strategies [49]. Today, digital preparation analysis (e.g., prepCheck, Dentsply Sirona) enables chairside control of the preparation and a real-time correction.…”
Section: Discussionmentioning
confidence: 99%